KONSEP KOSMOLOGI HINDU DALAM TEKS BHUANA KOSA - Sena, I Gusti Made Widya (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2017)
One of the truths implied in Scripture Veda is the doctrine or concept of cosmology (creation of the universe). Cosmology is one of the important knowledge in Hinduism, because cosmology not only provides knowledge about the creation of the universe, cosmology can further explain the nature of actual human will, which is still difficult to understand.Doctrine cosmology in Bali is expressed in local theology. Particularly lontar or texts Siwaistik always focuses on the teachings or knowledge of the Lord (Shiva) and knowledge of the way to achieve them as well as the creation of the universe, be it Bhuana Agung or Bhuana Alit.For this reason the right knowledge and also appropriately implement this concept, in particular the concept of Hindu cosmology in the text Bhuana Kosa very important to understanding in daily life towards a harmonious life and increased devotion to God.The concept of Hindu cosmology In the Text Bhuana Kosa is taking the concept of Tattwa Rudra. Tattwa Rudra occur from Shiva as the supreme reality, then united with Rudra became Purusa, of Purusa born Awyakta, of awyakta born Buddhi, of Buddhi (as a symbol of sattwam) was born Ahamkara / Ahangkara (symbol tattoo), then born Panca Tan Matra as a symbol tamas, manas (mind) and Panca Maha Bhuta.